Book of queens : the true story of the Middle Eastern horsewomen who fought the War on Terror - Mahdavi, Pardis, 1978- (Hachette Books, Hachette Book Group, 2023)
"Book of Queens reaches back centuries to the Persian Empire and a woman disguised as a man, facing an invading army, protected only by light armor and the stallion she sat astride. Mahdavi draws a thread from past to present: from her fearless Iranian grandmother, who guided survivors of domestic violence to independent mountain colonies in Afghanistan where the women, led by a general named Mina, became their country's first line of defense from marauding warlords. To the female warriors who helped train and breed the horses used by US Green Berets when they touched down in October 2001, with a mission but insufficient intelligence on the ground-women whose contributions were then forgotten. Pardis Mahdavi chases the legacy of Caspian horses and the women whose lives are saved by them, drawing on decades of research, newly-discovered diaries, and exclusive military sources. Among those intersecting stories is that of American Louise Firouz, who helped bring the breed back from the brink of extinction, connecting Virginia traders to British royals to the son of the Shah. Firouz's life is forever changed when she meets Mahdavi's own family, who run an unusual smuggling operation in addition to raising horses in a wild bid for freedom. Book of Queens is an epic tale of hidden women whose communal knowledge was instrumental in saving an animal as ancient as civilization, and who were the genesis of their own liberation"--